Effects of Wind-Driven Lateral Upwelling on Estuarine Carbonate Chemistry - Li, Ming; Li, Renjian; Cai, Wei-Jun; Testa, Jeremy M.; Shen, Chunqi (Frontiers in Marine Science, 2020)
Estuaries are productive ecosystems that support extensive vertebrate and invertebrate communities, but some have suffered from an accelerated pace of acidification in their bottom waters. A major challenge in the study of estuarine acidification is strong temporal and spatial variability of carbonate chemistry resulting from a wide array of physical forces such as winds, tides and river flows. Most past studies of carbonate system dynamics were limited to the along channel direction, while lateral dynamics received less attention. Recent observations in Chesapeake Bay showed strong lateral asymmetry in the partial pressure of carbon dioxide (pCO2) and air-sea CO2 flux during a single wind event, but comparable responses to different wind events has yet to be investigated. In this work, a coupled hydrodynamic-carbonate chemistry model is used to understand wind-driven variability in the estuarine carbonate system. It is found that wind-driven lateral upwelling ventilates high DIC (Dissolved Inorganic Carbon) and CO2 deep water and raises surface pCO2, thereby modifying the air-sea CO2 flux. The upwelling also advects low pH water onto the adjacent shoals and reduces the aragonite saturation state Ω_arag in these shallow water environments, producing large temporal pH fluctuations and low pH events. Regime diagrams are constructed to summarize the effects of wind events on temporal pH and Ω_arag fluctuations and the lateral gradients in DIC, pH and pCO2 in the estuary. This modeling study provides a mechanistic explanation for the observed wind-driven lateral variability in DIC and pCO2 and reproduces large pH and Ω_arag fluctuations that could be driven by physical forcing. Given that current and historic mainstem Bay oyster beds are located in shallow shoals affected by this upwelling, a large fraction of the oyster beds (100-300 km2) could be exposed to carbonate mineral under-saturated 〖(Ω〗_arag<1) conditions during wind events. This effect should be considered in the management of acidification-sensitive species in estuaries.